Phloem transport of structured RNAs: A widening repertoire of trafficking signals and protein factors. (October 2020) - Tolstyko, Eugeny A.; Lezzhov, Alexander A.; Morozov, Sergey Y.; Solovyev, Andrey G.
Highlights: Certain phloem-mobile RNAs contain phloem transport signals. Phloem transport signals are recognized by proteins directing RNA transport. The ability for phloem transport is reported for several classes of structured RNAs. 3D motifs in structured RNAs can serve as phloem transport signals. Abstract: The conducting sieve tubes of the phloem consist of sieve elements (SEs), which are enucleate cells incapable of transcription and translation. Nevertheless, SEs contain a large variety of RNAs, and long-distance RNA trafficking via the phloem has been documented. The phloem transport of certain RNAs, as well as the further unloading of these RNAs at target tissues, is essential for plant individual development and responses to environmental cues. The translocation of such RNAs via the phloem is believed to be directed by RNA structural elements serving as phloem transport signals (PTSs), which are recognized by proteins that direct the PTS-containing RNAs into the phloem translocation pathway. The ability of phloem transport has been reported for several classes of structured RNAs including viroids, genuine tRNAs, mRNAs with tRNA sequences embedded into mRNA untranslated regions, tRNA-like structures in the genomic RNAs of plant viruses, and micro-RNA (miRNA) precursors (pri-miRNA). Here, three distinct types of such RNAs are discussed, along with the proteins that may specifically interact with these structures in the phloem. Three-dimensional (3D) motifs, which are characteristic of imperfect RNA duplexes, are discussed as elements of phloem-mobile structured RNAs specifically recognized by proteins involved in phloem transport, thus serving as PTSs.